The Relationship between Teacher Training and the Use of Learning Media on Student Learning Achievement - Sholeh, Muh Ibnu; Ali, Himad; Ho, Pham Vu Phi; Sokip, Sokip; Syafii, Asrop; Sahri, Sahri; Wahrudin, Bambang; Muzakki, Hawwin (Southeast Asian Journal of Islamic Education, 2024)
This research aimed to determine the relationship between teacher training and the use of learning media on student learning achievement at MAN Tulungagung, Indonesia. This research used a quantitative approach with a correlational design. The research population was 243 teachers, and the sample was taken using the Slovin formula with an error rate of 5%, resulting in a sample of 151 respondents. The data collection technique used a questionnaire with a rating scale using a Likert scale. Data analysis techniques used linear regression analysis and multiple regression using SPSS software. The research results showed a positive and significant relationship between teacher training and student learning achievement (β = 0.37, p < 0.05). Likewise, there is a positive and significant relationship between the use of learning media and student learning achievement (β = 0.45, p < 0.05). Multiple regression analysis showed that these two factors simultaneously have a significant influence on student learning achievement (β_Teacher Training = 0.35, p < 0.05; β_Learning Media = 0.42, p < 0.05). The research results highlight the importance of improving teacher training quality and using innovative and effective learning media to improve student learning quality. The synergy of these two factors can create a more holistic and in-depth learning experience for students. Therefore, an integrated strategy of teacher training and learning media-based curriculum development can improve student achievement.